GENDER ANALYSIS OF COPING BEHAVIOUR, E-LIFESTYLE, AND HAPPINESS ON MILLENNIAL GENERATION IN COVID-19 PANDEMIC ERA - Intan Dwi Kurniawati; Herien Puspitawati (Journal of Child, Family, and Consumer Studies, 2022)
Changes that occur due to the Covid-19 pandemic are faced by all people, including the millennial generation. This study aims to analyze coping behavior, e- lifestyle, and happiness of the millennial generation during the Covid-19 pandemic based on gender. The research was conducted by a cross-sectional study using a non-probability voluntary sampling method. Data collection was carried out in April, and the study samples were obtained from 32 males and 68 females. Primary data was taken using a google form distributed to the millennial generation aged 22-41 years and living in Bogor, West Java. The location was chosen considering West Java has a happiness index (70.23) below the national happiness index (71.49) and is included in the five provinces with a low happiness index. The results of the descriptive analysis show that coping behavior, e- lifestyle, and happiness of the millennial generation during the Covid-19 pandemic are in the moderate category. The results of the different tests found no significant differences by gender in coping behavior, e-lifestyle, and millennial happiness. The SEM-PLS model shows that coping behavior significantly affects e- lifestyle. In addition, it was also found that coping behavior had a significant effect on the happiness of the millennial generation during the pandemic. Based on the results of this study, the happiness of the millennial generation during the Covid-19 pandemic is important, one of which is through coping behavior.